MEMBANGUN PEMAHAMAN TERHADAP KARYA SASTRA BERBENTUK FIKSI (Telaah Sifat dan Ragam Fiksi Naratif) - . Warsiman (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Some people who appreciate literature still discuss about the real meaning of each term which often appears in literary works especially in narrative fiction, such as plot, story, character, characterization, and conflict. The fact is there are some people who appreciate literature but are not able to differentiate those terms. That is why the purposeof this article is to explain the position of fiction, especially narrative fiction, in literary works. Because the characteristics of fiction include all the aspects of story, this article explains story, plot, and conflict. Story is an event followed by another event, then followed by another event, and so on, whereas plot is event series which is joined by causeand effect. Meanwhile, conflict is created by the interaction of each character. Without interaction, a conflict could not be created. Therefore, a conflict is an integral part that should be stated in. Whether good or bad a conflict is depends on the criteria of conflict itself.Keywords: fiksi, naratif, plot, cerita, tokoh, penokohan, konflik